Pengaruh Sikap dan Motivasi terhadap Minat Mahasiswa untuk Mengikuti Pendidikan Profesi Akuntan (PPAk) - Natami, Ni Made Anita Dewi; Muliartha, Ketut (E-Jurnal Akuntansi, 2019)
Knowing the influence of attitudes, quality motivation, and economic motivation on students' interest in joining PPAk is the purpose of this study. The research location is the Faculty of Economics and Business (FEB), Udayana University. The study sample consisted of 170 2015 class students majoring in accounting, of which 87 were regular students and 83 were non-regular students. The sampling technique used was purposive sampling using solvin formula. The data collection used is using questionnaires. Multiple linear regression analysis is the data analysis technique that used in this study. The results of data analysis found that attitudes, quality motivation, and economic motivation had a positive effect on students' interest in joining PPAk. Keywords: Attitudes; Quality Motivation; Economic Motivation; Interest in Following PPAk